A pragmatic and prudent consensus on the resurrection of extinct plant species using herbarium specimens. Issue 1 (9th November 2021) - Albani Rocchetti, Giulia; Davis, Charles; Caneva, Giulia; Bacchetta, Gianluigi; Fabrini, Giuseppe; Fenu, Giuseppe; Foggi, Bruno; Galasso, Gabriele; Gargano, Domenico; Giusso del Galdo, Gianpietro; Iberite, Mauro; Magrini, Sara; et al.
Abstract: Herbaria may represent remarkable sources of viable diaspores for recovering lost genetic variation and extinct plant species, but the application of rewilding extinct species using these collections has not been explored in detail. De‐extinction in plants may be achieved by germinating viable diaspores or culturing tissues preserved in herbarium specimens. Germination of old diaspores (fruits, seeds, spores) preserved in sub‐optimal uncontrolled storage conditions demonstrates that the recovery of extinct plants from herbarium specimens may be possible. Plant de‐extinction via herbarium specimens relies on the availability of samples containing viable diaspores, and on the inclination of curators and the conservation community to use such material for this purpose. We developed an internet‐based survey to assess (i) whether the scientific community would consent to the use of herbarium specimens of extinct species to attempt de‐extinction, and (ii) the limitations of removing diaspores from specimens. Despite the risk of potential damages to valuable specimens from historical collections when harvesting diaspores, a consensus for using specimens of extinct plant species emerged. Most respondents would permit the collection of a low number of diaspores, preferably from duplicate specimens and only if the integrity of the specimen is preserved. These considerations would be more restrictive for type specimens and those of historical value. These results help to formalise a decision framework for the grant and use of material from natural history collections and a pragmatic approach to attempt to resurrect extinct species from herbarium specimens.